2017
DOI: 10.3390/nu9010080
|View full text |Cite
|
Sign up to set email alerts
|

Social Dysfunction and Diet Outcomes in People with Psychosis

Abstract: This analysis aimed to examine the association of social dysfunction with food security status, fruit intake, vegetable intake, meal frequency and breakfast consumption in people with psychosis from the Hunter New England (HNE) catchment site of the Survey of High Impact Psychosis (SHIP). Social dysfunction and dietary information were collected using standardised tools. Independent binary logistic regressions were used to examine the association between social dysfunction and food security status, fruit intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Studies employed a range of methods. Two thirds of studies ( n = 38) employed a quantitative methodology, utilizing a survey or audit [1,2,7,16,34,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81], while the remainder ( n = 18) were qualitative. Thirteen studies used interviews [41,67,82,83,84,85,86,87,88,89,90,91], four studies employed focus groups [48,92,93,94], and one utilized photo voice [95].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies employed a range of methods. Two thirds of studies ( n = 38) employed a quantitative methodology, utilizing a survey or audit [1,2,7,16,34,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81], while the remainder ( n = 18) were qualitative. Thirteen studies used interviews [41,67,82,83,84,85,86,87,88,89,90,91], four studies employed focus groups [48,92,93,94], and one utilized photo voice [95].…”
Section: Resultsmentioning
confidence: 99%
“…The most common way to measure food insecurity was via the single item: “In the last 12 months, were there any times that you ran out of food and couldn’t afford to buy more?” This question has been criticized by many researchers for regularly under-reporting food insecurity in population-based studies [7,34]. This question (or a slight variation) was included in 22 studies [1,7,32,50,51,52,54,56,58,61,62,63,64,66,70,71,72,73,77,79,80,92]. Food insecurity measured by the single item ranged from 2.0%, reported in a study of older Australians [52], to 76%, reported in a study of food availability in remote Aboriginal communities [58].…”
Section: Resultsmentioning
confidence: 99%
“…A fourth study in Japan found men who had infrequent intakes of vegetables, mayonnaise, potatoes, soy products, seaweed and fish products had more pronounced psychiatric symptoms, although this correlation was not found in women. 76 Fruit and vegetable intake was found to be lower in the SMI group compared with controls/population data in three studies 48,52,62 and less than country/region-specific recommendations in nine studies 26,34,39,41,43,[52][53][54]63 and higher compared with the general population in one study. 77 Low intakes, or lower intakes than comparison groups, were found for fish 54,63 and nuts and vegetable oils.…”
Section: Qualitative Synthesismentioning
confidence: 99%
“…e brain structure location and neurobiological processes underlying these structural abnormalities are central to the pathophysiology of schizophrenia. Furthermore, alterations to the brain structure are linked to key psychotic symptoms (such as auditory hallucinations [9,10], neurosensory deficits [11,12], and social dysfunction [13,14] in SZ).…”
Section: Introductionmentioning
confidence: 99%